TECHNIQUES FOR MEASURING URANIUM-SERIES NUCLIDES: 1992-2002 - Goldstein S.J.; Stirling C.H. (My University, 2003)
Advances in geochemistry and geochronology are often closely linked to development of new technologies for improved measurement of elemental and isotopic abundance. At the beginning of the past decade, thermal ionization mass spectrometric (TIMS) methods were just beginning to be applied for long-lived uranium-series nuclide measurement (Edwards et al. 1987; Goldstein et al. 1989; Bard et al. 1990), with considerable advances in measurement speed, precision, and sensitivity over decay-counting methods. This opened up a vast number of applications in uranium-series geochronology and geochemistry of young sediments, volcanic rocks, and aqueous systems. Over the past decade there have continued to be advances in thermal ionization techniques, and the advent of alternative mass spectrometric methods, particularly multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS), has continued to improve the quality of uranium-series studies. So the past decade has been a particularly dynamic time for not only development of mass spectrometric techniques, but initiation of other methods related to long-lived uranium-series nuclide measurement. In the area of sample preparation, further development of microwave digestion methods had led to advances in speed and cost of analysis. In chemical separations, development of extraction chromatographic resins for isolating specific elements have simplified many separation problems and consequently improved analytical characteristics including sensitivity, speed of analysis, waste generation, and cost. With regard to instrumental analysis, advances in both decay-counting and mass spectrometry instrumentation have improved either measurement sensitivity or precision, speed of analysis, or analytical cost. One could argue that instrumental developments will continue to drive scientific breakthroughs in the application of uranium-series nuclides as tracers and chronometers in the earth and other sciences. In this chapter we discuss improvements documented in the literature over the past decade in these areas and others. Chemical procedures, decay-counting spectroscopy, and mass spectrometric techniques published prior to 1992 were …